Analysis of the Effect of Road Connectivity, Transportation Accessibility, and Activity Optimization on Public Services in Supporting Regional Economic Development in Lubuk Baja District, Batam City - Febi Hendra Masfar; Yuanita FD Sidabutar; Malahayati Rusli Bintang; Raymond Raymond; Ali Akbar (Majapahit Journal of Islamic Finance and Management, 2026)
Batam City, as part of the Batam–Bintan–Karimun (BBK) Free Trade Area, enjoys a strategic position along the international shipping route of the Strait of Malacca and plays a vital role in regional industrial and logistics activities. However, central trade and service areas such as Lubuk Baja District face serious challenges in terms of road connectivity, transportation accessibility, and the quality of public infrastructure. This study aims to analyze the influence of these three aspects on public services to support regional planning in the Lubuk Baja District. The method used is descriptive-quantitative, analyzing existing conditions and public perceptions. The results indicate that transportation connectivity and accessibility significantly influence the efficiency of mobility and economic activity. Integration of spatial planning policies and infrastructure management is necessary to achieve effective public services and sustainable regional development in Batam City